2022
DOI: 10.1097/ta.0000000000003681
|View full text |Cite
|
Sign up to set email alerts
|

Determining resuscitation outcomes in combat casualties: Design of the Deployed Hemostatic Emergency Resuscitation of Traumatic Exsanguinating Shock (Deployed HEROES) study

Abstract: BACKGROUND:During the course of the recent conflicts, the recommendations for resuscitation practices have evolved, but there has been no comprehensive comparative effectiveness study of these resuscitation strategies. The objective of this study was to describe the development and study design of the Deployed Hemostatic Emergency Resuscitation of Traumatic Exsanguinating Shock (Deployed HEROES) study-the first comprehensive analysis of military resuscitation practices in the deployed environment from October … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…Because this is not a Food and Drug Administration–approved product, these studies will likely not be performed. Investigators are looking retrospectively at the military experience to assess outcome differences between the types of whole blood 29 …”
Section: In-hospital Resuscitationmentioning
confidence: 99%
“…Because this is not a Food and Drug Administration–approved product, these studies will likely not be performed. Investigators are looking retrospectively at the military experience to assess outcome differences between the types of whole blood 29 …”
Section: In-hospital Resuscitationmentioning
confidence: 99%
“…[13][14][15][16][17] Despite the widespread use of UMT as an intervention for critical trauma patients, mortality rates remain as high as 40% to 80%. [13][14][15][16][17][18][19][20][21][22][23] Recognizing the limited availability of blood and the concerns surrounding ongoing transfusion in futile cases, studies have sought to investigate the concept of transfusion ceilings or cutoff point for high volume transfusion. 24,25 In 2022, Quintana et al 20 found a mortality plateau after 40.5 U, while Morris et al 22 in 2020 suggested futility after 80 U. Conversely, a military-focused study in 2023 by Gurney et al, 19 found a 24-hour mortality rate of only 20.7% for patients who received more than 100 U of blood.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20][21][22][23] Recognizing the limited availability of blood and the concerns surrounding ongoing transfusion in futile cases, studies have sought to investigate the concept of transfusion ceilings or cutoff point for high volume transfusion. 24,25 In 2022, Quintana et al 20 found a mortality plateau after 40.5 U, while Morris et al 22 in 2020 suggested futility after 80 U. Conversely, a military-focused study in 2023 by Gurney et al, 19 found a 24-hour mortality rate of only 20.7% for patients who received more than 100 U of blood. While this broad range of findings demonstrates the absence of a consensus threshold in our current literature, evidence does overarchingly support that increased blood product transfusion is not associated with increased survival and that the odds of mortality increase with increased products transfused.…”
mentioning
confidence: 99%
See 2 more Smart Citations